Understanding individual resilience in the workplace: the international collaboration of workforce resilience model - Rees, Clare S.; Breen, Lauren J.; Cusack, Lynette; Hegney, Desley (Frontiers in Psychology, 2015)
When not managed effectively, high levels of workplace stress can lead to several negative personal and performance outcomes. Some professional groups work in highly stressful settings and are therefore particularly at risk of conditions such as anxiety, depression, secondary traumatic stress and burnout. However, some individuals are less affected by workplace stress and the associated negative outcomes. Such individuals have been described as ‘resilient’. A number of studies have found relationships between levels of individual resilience and specific negative outcomes such as burnout and compassion fatigue. However, because psychological resilience is a multi-dimensional construct it is necessary to more clearly delineate it from other related and overlapping constructs. The creation of a testable theoretical model of individual workforce resilience, which includes both stable traits (e.g. neuroticism) as well as more malleable intrapersonal factors (e.g. coping style), enables information to be derived that can eventually inform interventions aimed at enhancing individual resilience in the workplace. The purpose of this paper is to introduce a new theoretical model of individual workforce resilience that includes several intrapersonal constructs known to be central in the appraisal of and response to stressors and that also overlap with the construct of psychological resilience. We propose a model in which psychological resilience is hypothesised to mediate the relationship between neuroticism, mindfulness, self-efficacy, coping and psychological adjustment.